Evaluasi Dampak Kebijakan Pemekaran Daerah di Indonesia: Studi Daerah Pemekaran Kabupaten Solok Selatan - Yusran, Rahmadani (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2007)
Â This article tries to describe the impact of territory separation of Solok Regency in West Sumatera. Moreover, this article will try to evaluate and to analyze whether the policy of territory separation has a good or bad impact toward job performace ofÂ Solok government. This study become more important to do because there are many significant issues that influence the job performance of Solok government in the newer Solok territory. This study has been conducted through a qualitative approach. Â Kata kunci : Evaluasi, Dampak Kebijakan, Pembangunan, Pemekaran, Pelayanan Publik, Pemberdayaan Masyarakat